Toward a Systemic View to Cost Overrun Causation in Infrastructure Projects: A Review and Implications for Research - Ahiaga-Dagbui, D.; Love, Peter; Smith, S.; Ackermann, Fran (Jossey Bass, Ed. & Pub., 2016)
Infrastructure cost overruns receive significant amount of attention in the academic literature as well as the popular press. The methodological weaknesses in the dominant approaches adopted to explain cost overrun causation on infrastructure projects are explored in this paper. A considerable amount of cost overrun research is superficial, replicative and thus stagnated the development of a robust theory to mitigate and contain the problem. Future research should move from single-cause identification and the traditional net-effect correlational analysis to a search for causal recipes through systems thinking and retrospective sensemaking to address the high-level interactions between multiple factors.